The Pro-inflammatory IL6 and serum glucose in Polycystic Ovary Syndrome - AL-Hadithi, Hayfaa S.; Al-Derzi, Aida R. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Polycystic ovary syndrome (PCOS) is one of the most common female endocrine disorders. PCOS produces symptoms in approximately 5% to 10% of women of reproductive age (12–45 years old). Objective: To detect the level of IL-6 in PCOS patients correlated with their serum glucose. Patients and methods: This is a prospective study carried out at Baghdad teaching hospital in Baghdad/Iraq from November 2011 to January 2012. In this study, 80 blood samples (40 untreated women with PCOS cases and 40 healthy control) were collected to investigate their IL-6 levels by using Enzyme linked immunosorbent assay (ELISA) technique and fasting blood sugar (FBS) by enzymatic assay. Results: Serum IL-6 elevated in PCOS patients mainly those with high blood sugar. Conclusion: Serum IL-6 levels were significantly higher among PCOS women than in healthy group. PCOS patients had high blood sugar when compared to control group. Significant statistical positive association was seen between serum IL-6 level and FBS among study cases.